Strategi Pembelajaran Dalam “Go Sport” Kurikulum Pendidikan Karakter - Aslan, Aslan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
Character education is a system created by educators. The first and foremost education in making the system is the parents, the two teachers, the three communities. To see a significant success, then the first education of parents is very decisive from the educational values ​​of these characters. The existence of teaching the values ​​of character education to the child from the parent, thus continuing further education which is assumed by the teacher, resides to form the value to be personality on him, so that the curriculum